Proximal tubular renal dysfunction among HIV infected patients on Tenofovir versus Tenofovir sparing regimen in western Kenya - Mercy Jelagat Karoney; Mathew Kirtptonui Koech; Evangeline Wawira Njiru; Willis Dixon Owino Ong’or (PLoS ONE, 2022)
Introduction Tenofovir Disoproxil Fumarate (TDF) is the most widely used Anti-Retroviral Therapy (ART) drug due to its potency, safety profile and World Health Organization (WHO) recommendation. TDF causes proximal tubular renal dysfunction (PTRD) leading to Fanconi syndrome, acute kidney injury and chronic kidney disease. Modest rates (2–4%) of TDF related toxicity based on estimated Glomerular Filtration Rate (GFR) have been described, while TDF-induced PTRD has been reported to be 22%. TDF toxicity is more likely among African patients, it is reversible and TDF may be renal dosed in patients with dysfunction. The objective of this study was to assess proximal tubular renal dysfunction, global renal function, and their determinants among patients on TDF versus TDF-sparing regimen. Methods This was a cross-sectional study among people living with HIV/AIDS (PLWHA) attending the Academic Model Providing Access to Healthcare (AMPATH) program. The primary outcome of interest in this study was PTRD while the secondary outcome of interest was estimated GFR. PTRD was defined as any two of beta-2 microglobulin in urine, metabolic acidosis, normoglycemic glucosuria and fractional excretion of phosphate. Student’s t-test, chi-square and their non-parametric equivalents were used to test for statistical significance. Univariate and multivariate logistic regression analysis was carried out. Results A total of 516 participants were included in the final analysis, 261 on TDF while 255 were on TDF-sparing regimens. The mean (SD) age of all participants was 41.5 (12.6) years with majority being female (60.3%). The proportion of PTRD was 10.0% versus 3.1% in the TDF compared to TDF-sparing group (P<0.001). Mean estimated GFR was 112.8 (21.5) vs 109.7 (21.9) ml/min/1.73mm3 (P = 0.20) for the TDF compared to TDF-sparing group. TDF users were more likely to have PTRD compared to non-TDF users, adjusted Odds Ratio (AOR) 3.0, 95% CI 1.12 to 7.75. Conclusion There was significant PTRD in the TDF compared to TDF-sparing group without significant difference in estimated GFR. The clinical significance of these findings may not be clear in the short term.